Performance evaluation of MAC protocols for cooperative MIMO transmissions in sensor networks - Ahmad, Mohd Riduan; Dutkiewicz, Eryk; Huang, Xiaojing (2008)
Cooperative Multiple-Input Multiple-Output (MIMO) schemes can reduce both transmission energy and latency in distributed wireless sensor networks (WSNs). In this paper we develop a new cooperative low power listening (LPL) Medium Access Control (MAC) protocol for two cooperative MIMO schemes: optimal Beamforming (BF) and Spatial Multiplexing (SM). We develop analytical models for the total energy consumption and retransmission rates for both schemes and analyse the proposed MAC protocol in term of total energy consumption. The impact of the check interval and the number of cooperative transmitting nodes, M and cooperative receiving nodes N on the total energy consumption are investigated. We show that the new cooperative MAC with the optimal Beamforming scheme outperforms the other cooperative and SISO schemes in term of total energy consumption with the number of cooperating nodes set to M=2.